Investigating Public Hesitation In Paying Taxes - Krisnawati, Lenny (Jurnal Ekonomi dan Bisnis Jagaditha, 2021)
Taxes are the biggest contributor to the state budget portion, but unfortunately the level of public awareness in paying taxes is still very low. The purpose of this study is to investigate the causes of public hesitation in reporting the Annual Tax Return (SPT) and making tax payments, especially for non-employee taxpayers at KPP Pratama Denpasar Timur (Denpasar Timur Tax Office). This research uses a qualitative approach method with purposive sampling technique. The location of this research is at Denpasar Timur Tax Office. The reason for choosing this location is because the Denpasar Timur Tax Office is located in the center of Denpasar city which has a large number of taxpayers with various business classifications, and for the tax year 2018 to 2020 there has been a significant decrease in the number of annual tax returns and tax payments from previous years. Data collection was carried out by in-depth interviews and through virtual interviews, observations and document analysis. The interviewees in this study were non-employee individual taxpayers who were registered at KPP Pratama Denpasar Timur with the criteria of obeying the payment and reporting of Annual SPT, often late in making payments and reporting of Annual SPT, and taxpayers with the criteria of never making payments and reporting the Annual SPT. From the research results, data shows that public doubts in paying taxes are influenced by the absence of direct remuneration received by taxpayers, the covid-19 pandemic that paralyzed most of the community's economy, limited knowledge and understanding of taxation and the limited ability of taxpayers to utilize online facilities which has been provided by the Directorate General of Taxes